2008
DOI: 10.1038/tpj.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

DRD4 48 bp VNTR but not 5-HT2C Cys23Ser receptor polymorphism is related to antipsychotic-induced weight gain

Abstract: Weight gain is a major side effect of antipsychotic treatment. The antidopaminergic and antiserotonergic effect of antipsychotics may contribute to antipsychotic-induced weight gain. We, therefore conducted a prospective clinical study, to investigate whether the D4 receptor (DRD4) 48 bp (base pair) variable number of tandem repeat (VNTR) polymorphism and the 5-hydroxytryptamine 2C receptor (HT 2C ) cysteine for serine substitution at position 23 (Cys23Ser) polymorphism may influence weight gain during antipsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
(35 reference statements)
1
14
0
2
Order By: Relevance
“…In the following studies, several genetic variants have been reported to be associated with BWG during AAP treatment, such as genetic variants in HTR2C, HTR2A, HTR6, DRD4, GNB3, INSIG2, BDNF, LEP, SNP25, and ADRA2A (Reynolds et al 2002;Wang et al 2005;Ujike et al 2008;Le Hellard et al 2009;Lane et al 2006;Popp et al 2009;Calarge et al 2009;Müller et al 2005;Sickert et al 2009); however, replication in larger, independent samples is required to confirm these findings.…”
Section: Introductionmentioning
confidence: 92%
“…In the following studies, several genetic variants have been reported to be associated with BWG during AAP treatment, such as genetic variants in HTR2C, HTR2A, HTR6, DRD4, GNB3, INSIG2, BDNF, LEP, SNP25, and ADRA2A (Reynolds et al 2002;Wang et al 2005;Ujike et al 2008;Le Hellard et al 2009;Lane et al 2006;Popp et al 2009;Calarge et al 2009;Müller et al 2005;Sickert et al 2009); however, replication in larger, independent samples is required to confirm these findings.…”
Section: Introductionmentioning
confidence: 92%
“…Candidate gene studies have produced significant findings in the 5-HTR2C, GNB3, ADR2A and DRD4 receptors. 10,46 Weight gain under olanzapine therapy was significantly lower for 5-HTR2C À759T-allele carriers (0.9 vs 3.9% for others within 4 weeks, P ¼ 0.011). This is in accordance with the results of several previous studies, which have shown a significant influence of this polymorphism on weight gain under olanzapine therapy.…”
Section: Genotypes and Weight Gainmentioning
confidence: 98%
“…[17,21,33,34,36,54,55,58, Of these, 11 articles tested the hypothesis that ketamine worsens the symptoms of schizophrenia [21,55,92,93,103,106,109,125,127,131,150] and these were excluded from the analysis. Thirty-three publications without placebo comparisons, [33,34,36,78,79,82,90,91,94,101,110,112,[120][121][122]126,136,138,139,[141][142][143]146,[151][152][153][156][157][158][159][160]…”
Section: Study Selectionmentioning
confidence: 99%